PREFERENSI KEPUTUSAN MEMBAYAR ZAKAT, INFAQ, SEDEKAH DI LEMBAGA AMIL ZAKAT MELALUI PEMBAYARAN DIGITAL - Nabilah, Ulfa; Galuh, Ajeng Kartika (Islamic Economics and finance in Focus, 2023)
The high number of Muslim population and the potential for Zakat, Infaq and Alms (ZIS) in Indonesia do not reflect the collection of ZIS in Indonesia by the Amil Zakat Institution (LAZ). Efforts to maximize ZIS collection by LAZ require innovation in the form of digital payment methods. The purpose of this research is to find out the preferences of muzakki in channeling ZIS funds through digital payments to LAZ based on LAZ's reputation in the community, the ZIS distribution program to mustahiq, the convenience offered on LAZ digital payments, and the digital ZIS payment method by muzakki. The method in this study is quantitative by using logistic regression data analysis. The results of this study partially LAZ reputation variables and digital ZIS payment methods have a significant and positive effect on the decision to pay ZIS through digital payments. Simultaneously the LAZ reputation variable, ZIS distribution program, convenience, and digital ZIS payment methods have a significant effect on the decision to pay ZIS through digital payments. So, from this research it can be seen that muzakki's trust and the development of digital payment technology offered by LAZ have influenced muzakki's interest in paying ZIS at the LAZ.